Ethanol extracts of Rhaponticum uniflorum (L.) DC inflorescence ameliorate LPS-mediated acute lung injury by alleviating inflammatory responses via the Nrf2/HO-1 signaling pathway. (5th October 2022) - Zhen, Dong; Liu, Chunyan; Huang, Tianpeng; Fu, Danni; Bai, Xue; Ma, Qianqian; Jiang, Mingyang; Gong, Guohua
Abstract: Ethnopharmacological relevance: Rhaponticum uniflorum (L.) DC is a member of the Compositae family. Loulu flowers (LLF) is the inflorescence of this plant, which is a commonly used Mongolian medicine for the treatment of inflammatory diseases due to its heat-clearing and detoxifying properties. It is used caused by. However, its anti-inflammatory mechanisms are not clear. Aim of this study : We investigated whether ethanol extracts of LLF can alleviate LPS-induced acute lung injury and explored the mechanism involved. Material and methods: BALB/C mice were intragastrically administered with sodium carboxymethyl cellulose (0.5%, 1 mL/100 g) or ethanol extracts of LLF at a dose of 100, 200, and 400 mg/kg, once daily, for 3 days. Subsequently, mice models of acute lung injury were established by LPS and used for the determination of anti-inflammatory effects of LLF. After 6 h of treatment, mice were sacrificed to collect lung tissues and bronchoalveolar lavage fluid (BALF). H&E staining assay was performed on the tissues for pathological analysis. The ELISA test was conducted to measure NO, IL-6, TNF-α, MPO, SOD, CAT, MDA and GSH-PX levels. The expression level of proteins associated with the Nrf2/HO-1 and MAPK/NF-κB signaling pathways were determined using Western blot analysis. Levels of F4/80 and Nrf2 in lungs were quantified using immunohistochemistry. Results: Oral administration of LLF extracts alleviated LPS-induced pathological alterations, reduced lung W/D weight ratio, decreased levels of TP, pro-inflammatory factors (TNF-α and IL-6), and NO in BALF. Pretreatment with LLF extract downregulated F4/80 expression in lung tissue and suppressed LPS-induced elevations in BALF and lung tissue levels of MPO. Moreover, treatment with LLF extract reduced the expression level of proteins associated with the MAPK signaling pathway (p-p38, p-JNK, p-ERK) and TLR4/NF-κB signaling pathways (TLR4, Myd88, p-IκB, p-p65). Moreover, LLF extract upregulated Nrf2, HO-1 and NQO1 protein levels, downregulated Keap1 protein level. Immunohistochemical analysis revealed that LLF reduced the LPS-induced increase in Nfr2 expression in lung tissues. Conclusion: Ethanol extracts of LLF ameliorated LPS-induced acute lung injury by suppressing inflammatory response and enhancing antioxidation capacity, which correlated with the MAPK/NF-κB and Nfr2/HO-1 signaling pathways. Graphical abstract: Image 1 Highlights: LLF showed protective effects on LPS-induced acute lung injury (ALI). The protective effects of LLF on LPS-induced ALI are associated with inhibited NF-κB and MAPK signaling pathway. LLF attenuates LPS-induced ALI by promoting the antioxidant capacity through regulating the Nrf2/HO-1 signaling pathway.